Interatrial block and ischemic stroke - Lindow, Thomas; Baranchuk, Adrian (Journal of Thoracic Disease, 2018)
Cardiac embolism is a common cause of ischemic stroke. Atrial fibrillation (AF) can be detected in nearly 25% of all patients with stroke by sequentially combining different electrocardiographic methods (1). Advanced IAB (aIAB) has been described to predict occurrence of new onset and recurrent AF (2). We describe a case of a patient in whom detection of atypical aIAB motivated extended cardiac monitoring resulting in the diagnosis of paroxysmal AF and a subsequent decision on full oral anticoagulation strategy.